OWL Consistency Models in Smart Contracts Design - Davila, Rene; Aldeco Perez, Rocio; Barcenas, Everardo (International Journal of Combinatorial Optimization Problems and Informatics, 2026)
Smart Contracts are stored and executed on a Blockchain network, thereby automatically enforcing the predefined rules once the execution conditions are satisfied. Hence, if the contract incorporates contradictory design rules, it may result in unforeseen outcomes within the blockchain environment. Accordingly, this proposal models the rules embedded in a Smart Contract through the Web Ontology Language (OWL), by applying the formal definition of consistency within a verification framework grounded in Description Logics. Smart citations: https://scite.ai/reports/10.61467/2007.1558.2026.v17i2.1258 Dimensions. Open Alex.